STRATEGI PENGEMBANGAN SISTEM AGRIBISNIS KELAPA SAWIT (Elaeis Guineensis Jacq) DI KABUPATEN LABUHAN BATU UTARA - Bambang Hermanto; Sri Wahyuni (Universitas Batam, 2021)
The purpose of this research is to find out what are the strengths, weaknesses, opportunities, and threats in the strategy of developing an oil palm agribusiness system (Elaeis Guineensis Jacq) in North Labuhan Batu Regency. The sampling research method used is purposive sampling method. The data used are primary data and secondary data. The analytical method used is descriptive quantitative method using SWOT analysis by analyzing the IFAS (Internal Factor Analysis Summary) and EFAS (External Factor Analysis Summary) factors. The results showed that using the SWOT diagram matrix, the oil palm agribusiness system development strategy was found in area II (Diversification Strategy). The situation in area II is a situation where farmers have to change their previous strategy, because the development of oil palm faces various threats but oil palm farmers still have internal strength. The focus of the strategy is to take action using strengths to take advantage of long-term opportunities by means of product and market diversification strategies.